2019
DOI: 10.15561/18189172.2019.0107
|View full text |Cite
|
Sign up to set email alerts
|

The development of speed-power qualities of schoolchildren with different typologies applying coordination training

Abstract: Purpose : to determine the influence of coordination abilities on the development of speed-power qualities in 7-8 years old schoolchildren with a different type of nervous system. Material : the pedagogical experiment was conducted in a regular school and lasted 7 months. The study involved children 7-8 years old (n = 60). All schoolchildren were differentiated into 3 groups (in each group - n = 20). Coordination abilities were determined by the test “3x10 shuttle run”. Speed- power qualities were determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
2
12
0
4
Order By: Relevance
“…As a rule, the standard physical education program at school covers the entire range of active and versatile activities of schoolchildren 1 . In previous studies, we have proved the effectiveness of introducing a set of exercises aimed at developing speed and strength abilities in children aged 13-14 years into the educational process of physical education of schoolchildren 5 . Such a complex helps to purposefully influence the speed and strength abilities of schoolchildren and significantly increase them in this age period, which is favorable for their development [6][7][8] .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…As a rule, the standard physical education program at school covers the entire range of active and versatile activities of schoolchildren 1 . In previous studies, we have proved the effectiveness of introducing a set of exercises aimed at developing speed and strength abilities in children aged 13-14 years into the educational process of physical education of schoolchildren 5 . Such a complex helps to purposefully influence the speed and strength abilities of schoolchildren and significantly increase them in this age period, which is favorable for their development [6][7][8] .…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, we have shown the effect of coordination training on indicators of other physical abilities in primary school children 5 . However, if coordination abilities or motor skills should be purposefully developed in primary school age, then middle and high school age is favorable for the development of speed-strength abilities [6][7][8] .…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…В ранее проведенных исследованиях мы подтвердили взаимосвязь координационных способностей, их влияние на развитие других физических способностей [8]. Однако моторные и координационные навыки интенсивнее формируются в младшем школьном возрасте, а в среднем звене следует уделить внимание развитию других показателей.…”
unclassified